Penyuluhan Pendidikan Penyadaran Lingkungan Untuk Mendukung Pelaksanaan Program Adiwiyata Di SDN Inpres Kampus Tamalanrea Kota Makassar - Achmad Zubair -; Roslinda Ibrahim; Asiyanti T. Lando; Irwan Ridwan; Kartika Sari; Nurjannah Oktorina (Faculty of Engineering UNHAS, 2020)
The environmental problems that often occur around us, through education is expected to be able to instill the care of the younger generation to protect the environment, because the younger generation is the heir to the inhabitants of the earth in the future. Base on the Indonesian regulation, number 32 (2009) said that everyone has the right and role in environmental management. This means that every individual must have a sense of responsibility towards the environment and a caring attitude to protect the environment. The purpose of this activity is to increase the knowledge and insight of students regarding environmental awareness education to support the implementation of the adiwiyata program. The level of concern and participation of school members in the field of environmental preservation is already quite high, but the level of concern still needs to be improved so that it can influence knowledge and behavior continuously and encourage widespread activities or concrete actions in efforts to improve the Unhas State Inpres SD State Elementary School. The method used to achieve the stated goals and targets is to carry out training and counseling that are expected to be useful for students and teachers. With the implementation of this community service activity, the knowledge of students and teachers about environmental awareness education to support the implementation of the adiwiyata program increases. Knowledge and skills possessed are expected to be transmitted and become an example for elementary schools around Makassar City.